Autoimmunity against cardiac troponin I in ischaemia reperfusion injury - Volz, Hans Christian; Buß, Sebastian Johannes; Li, Jin; Göser, Stefan; Andrassy, Martin; Öttl, Renate; Pfitzer, Gabriele; Katus, Hugo; Kaya, Ziya (European journal of heart failure, 2011)
Aims Autoimmunity against cardiac troponin I (cTnI) has deleterious effects on the infarcted myocardium early after onset of ischaemia. Here, we explored the impact of cTnI-autoimmunity in the long term. Furthermore, we studied the effects of cTnI-autoimmunity on the infarcted myocardium following revascularization measures in terms of ischaemia reperfusion injury (IRI), which resembles clinical reality more closely. Methods and results After immunization with either cTnI (n= 10) or a control buffer (n= 14), A/J mice underwent chronic coronary artery ligation. Another group of mice immunized with cTnI (n= 13) underwent temporary coronary artery occlusion and were compared with non-immunized controls (n= 17). Left ventricular function was evaluated by echocardiography. Hearts were obtained for histological evaluation. Immunological responses were quantified by analysis of cytokine and chemokine patterns as well as anti-cTnI antibody titres. Myocardial inflammation and cardiac dysfunction were detectable as late as 180 days after myocardial infarction (MI). Previous cTnI-immunization enhanced myocardial inflammation and dysfunction. Mice subjected to cTnI-immunization before IRI exhibited a higher inflammation score, an upregulated expression of pro-inflammatory chemokines (IP-10, MIP-1, Ltn, RANTES, TCA-3) and chemokine receptors (CCR2, CCR5), increased interleukin (IL)-2, interferon (IFN)-g, and decreased IL-10 production along with a markedly reduced fractional shortening after IRI compared with the controls. Conclusion Our results demonstrate for the first time that cTnI-induced autoimmune response not only leads to increased myocardial inflammation and impaired cardiac function 180 days after chronic coronary artery ligation, but also exacerbates ischaemia/reperfusion injury compared with non-immunized controls. Hence, the presence of cTnI-autoimmunity could render subjects more vulnerable to prospective myocardial injury, be it MI, or secondary revascularization measures.
Erstmals veröffentlicht: 18 February 2014
Gesehen am 27.10.2022